Daucosterol inhibits colon cancer growth by inducing apoptosis, inhibiting cell migration and invasion and targeting caspase signalling pathway (Bangladesh Journal of Pharmacology, 2016)
The aim of the present investigation was to examine and demonstrate in detail the anti-cancer and apoptotic effects of daucosterol in human colon cancer cell line HCT-116. The effects of this compound on cell migration, cell invasion, cell cycle analysis and caspase signalling pathway were also studied. Cell viability was evaluated by MTT assay using different doses of the drug. In vitro wound healing assay was used to study cell migration. Flow cytometry was involved to examine cell apoptosis as well as cell cycle phase distribution. Daucosterol induced significant, dose-dependent as well as time-dependent cytotoxic effects with IC50 values of 26.6 and 47.3 µM at 24 and 48 hours time intervals respectively. The percent of cells that migrated decreased from 99% in case of untreated control to 84.2, 45.2, 39.5 and 14.4% in groups treated with 0, 5, 50, 75 and 100 µM of daucosterol respectively. Percentage of apoptotic cells increased from 2.5% in untreated control cells to 23.6, 46.9 and 74.2% in cells treated with 5, 50 and 100 µM dose of daucosterol respectively. Daucosterol at different doses induced cell cycle arrest at sub-G1 phase of the cell cycle.Video Clip of Methodology:Cell Migration Assay: 1 min   Full Screen   Alternate